2019
DOI: 10.1021/acs.analchem.9b02093
|View full text |Cite
|
Sign up to set email alerts
|

CI-Orbitrap: An Analytical Instrument To Study Atmospheric Reactive Organic Species

Abstract: While acknowledged as key components in the formation of new particles in the atmosphere, the accurate characterization of gaseous (highly) oxygenated organic compounds remains challenging, and requires analytical developments. Earlier studies have successfully used the nitrate ion (NO3 -) based chemical ionization (CI) coupled to atmospheric pressure interface time-of-flight mass spectrometry (CI-APi-TOF) for monitoring these compounds. Despite many breakthroughs in recent years, the CI-APi-TOF has many limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 35 publications
(101 reference statements)
0
52
0
Order By: Relevance
“…In general, dimers appear to bind more strongly to NO 3than do monomers ( Supplementary Figs. 2c and 3c) 44 . In Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In general, dimers appear to bind more strongly to NO 3than do monomers ( Supplementary Figs. 2c and 3c) 44 . In Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Negligible particle formation (<100 cm −3 ) was observed by a condensation particle counter (TSI CPC 3772) during all experiments. A Q Exactive Orbitrap mass spectrometer (Thermo Scientific, US) coupled to an atmospheric pressure CI inlet 44 was used for online analysis of ozonolysis products. The Orbitrap has been used with an automatic gain control (AGC) and maximum injection time set to 1 × 10 5 and 3000 ms, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational approaches, including ion deconvolution procedures, are required to partly resolve this limitation in order to extract the maximum possible information content (Cubison and Jimenez, 2015;Meija and Caruso, 2004;Zhang et al, 2019aZhang et al, , 2019b). To overcome these limitations, we have coupled a high-resolution mass spectrometer (Orbitrap, Eliuk and Makarov 2015) with a CI source (Riva et al, 2019a(Riva et al, , 2020 and an extractive ESI (EESI) inlet (Lee et al, 2020) for online analysis. Similarly, Zuth et al (2018) have combined an atmospheric pressure chemical ionization (APCI) interface to an Orbitrap and have shown that such a technology can achieve much greater mass resolving power at similar detection limit for the real-time measurement of organic aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…The demand for a new software tool for analyzing Orbitrap data comes along with applying an Orbitrap in long-term continuous online measurements. The commercial software, Xcalibur TM that has been used in our initial studies (Lee et al, 2020;Riva et al, 2019aRiva et al, , 2020, provides an interface for basic data analysis e.g., reading single or averaged scans and exporting the time evolution of selected signal peaks. However, more complicated data analysis is usually needed for investigating the complexity and chemical processes occurring within the atmosphere.…”
Section: Introductionmentioning
confidence: 99%